A facile chemical synthesis of nanoflake NiS2 layers and their photocatalytic activity. Issue 17 (5th April 2022) - Gomaa, Mohammed M.; Sayed, Mohamed H.; Abdel-Wahed, Mahmoud S.; Boshta, Mostafa
Abstract : A single phase nanoflake NiS2 layer synthesized by a facile chemical bath deposition showed good solar light photocatalytic degradation of phenol with good stability and reusability. Abstract : A single-phase and crystalline NiS2 nanoflake layer was produced by a facile and novel approach consisting of a two-step growth process. First, a Ni(OH)2 layer was synthesized by a chemical bath deposition approach using a nickel precursor and ammonia as the starting solution. In a second step, the obtained Ni(OH)2 layer was transformed into a NiS2 layer by a sulfurization process at 450 °C for 1 h. The XRD analysis showed a single-phase NiS2 layer with no additional peaks related to any secondary phases. Raman and X-ray photoelectron spectroscopy further confirmed the formation of a single-phase NiS2 layer. SEM revealed that the NiS2 layer consisted of overlapping nanoflakes. The optical bandgap of the NiS2 layer was evaluated with the Kubelka–Munk function from the diffuse reflectance spectrum (DRS) and was estimated to be around 1.19 eV, making NiS2 suitable for the photodegradation of organic pollutants under solar light. The NiS2 nanoflake layer showed photocatalytic activity for the degradation of phenol under solar irradiation at natural pH 6. The NiS2 nanoflake layer exhibited good solar light photocatalytic activity in the photodegradation of phenol as a model organic pollutant.